PENGARUH KEADILAN ORGANISASI TERHADAP EMOSI POSITIP PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI TENGAH - Tompodung, Julviane Anita Beatrix (Katalogis, 2019)
The aim of this study is to explore the effect of organizational justice (distributive justice, procedural justice, interactional justice) toward employee emotion in BPKAD Cental Sulawesi Province. A survey was used to test the model in the context of organizational justice with the help of multistage random sampling. In total, 101 participant which was employee of BPKAD Cental Sulawesi Province completed the questionnaire. Multiple regression analysis was performed to test the total effect of organizational justice (distributive justice, procedural justice, interactional justice) toward employee emotion in BPKAD Cental Sulawesi Province. Results showed that organizational justice (distributive justice, procedural justice, interactional justice) influence the employee emotion in BPKAD Cental Sulawesi Province simultaneously. Partially, distributive justice, procedural justice and interactional justice influence employee emotion. Thus, all the hypotheses in this study were supported.